Legal appraisal of current legislation to conserve biodiversity of wetlands in Malaysia - Irini Ibrahim (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2017)
Wetlands, known as the kidneys of the earth are an important environmental element which are being destroyed and disappearing at a fast pace. In the past 40 years, over 40% of wetlands habitats have been lost and 76% of all wetland species have been damaged or threatened all over the world. In Malaysia, destruction and threats to the wetlands ecosystem have adverse effect on the conservation of biodiversity of wetlands. Large scale land reclamation for agriculture or development and nonsustainable logging has been identified as one of the major threat to wetland. Therefore, this research examines the adequacy of the current legal framework for the conservation of biodiversity of wetlands in Malaysia. The objectives of the research are to investigate protection of wetlands under the current legal framework in Malaysia and the application of conservation of biodiversity of wetlands. The extent of implementation of international legal environmental norms on wetlands and conservation i.e. the Ramsar Convention on Wetlands and the Convention of Biodiversity (CBD) are also examined while the practices and experiences of conservation in other jurisdiction such as Australia is also discussed. The research adopted a qualitative method to investigate its objectives. Primary data was collected from two designated Ramsar sites in Malaysia. In addition, interviews were conducted to ascertain wetlands conservation practice and law. The research found that the current laws in Malaysia seem to lack adequate provision for wetland conservation. The research is significant as it contributes to the existing body of knowledge in conservation of wetlands and specifically charts a new course on the legal discourse on the biodiversity of wetlands conservation in Malaysia.